Four-penta-graphenes: Novel two-dimensional fenestrane-based auxetic nanocarbon allotropes for nanoelectronics and optoelectronics. (15th August 2022) - Kilic, Mehmet Emin; Lee, Kwang-Ryeol
Abstract: The great success of graphene has encouraged tremendous interest in searching for new two-dimensional (2D) carbon allotropes. Based on first-principles calculations, we proposed new 2D carbon allotropes obtained from the assembly of fenestrane molecule unit, named as four-penta-graphenes (fPG). The fPG monolayers are energetically more favorable than pentagraphene and show excellent dynamical, thermal, and mechanical stability. They exhibit exotic mechanical properties including anisotropic in-plane stiffness and auxetic behavior with sign-tunable Poisson's ratio. Their electronic properties are diverse, ranging from narrow band gap semiconductors to metal. The electronic band gap and band edge positions of the fPG semiconductors can be flexibly modulated by strain engineering. Indirect-to-direct band gap and semiconductor-to-metal transitions can be achieved by applying compressive and tensile strains, respectively. High mobility and anisotropic effective mass of carriers make these materials promising for nanoelectronics. Using many-body GW0 +BSE approximations, we reveal that the fPG semiconductors exhibit strong excitonic effects with distinct optical absorption peaks in the visible range. These remarkable optical properties make them also promising devices for optoelectronics. Graphical abstract: Image 1